In vitro cytotoxic effect of Cleistanthus collinus extracts and fractions on mouse cell line - Thamburaj Suman, Ramaraj Elangomathavan, Soundherrajan Ilavenil and Samiraj Ramesh (Journal of Applied Pharmaceutical Science, 2014)
Aqueous, methanol and ethyl acetate crude extracts and fractions were prepared using Cleistanthus collinus Roxb. dry leaf powder. All the extracts and fractions were subjected to in vitro cytotoxic analysis using mouse 3T3- L1 pre-adipocytes cell line. Rate of cell proliferation was calculated to determine the anti-proliferative activity. Aqueous, methanol and ethyl acetate extracts (≥100 µg/ml) significantly control cell proliferation at 48 hr incubation. However, fractions exhibited higher level of toxicity and affect cell growth even at 50 µg/ml concentration within 28 hr incubation. Fractions obtained from methanol extract showed cytotoxic effect about 43-76 % at 50-250 µg/ml at 48 hr incubation (Concentration necessary to inhibit cell growth at 50 % is ~75 µg/ml). Followed by, ethyl acetate fraction exhibited 23-59 % of anti-proliferative activity (Concentration necessary to inhibit cell growth at 50 % is ~180 µg/ml). It may be concluded that promising fractions of C. collinus with higher toxicity level could be exploited for pharmacological purposes.
Keywords: Cleistanthus, cytotoxic, fractions, leaf extracts, mouse cells.